Implementation of Liveworksheet-Based Interactive E-Modules in Learning Islamic Education to Increase Student Motivation - Mitra, Siti Nuraeni; Wahyudin, Didin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Islamic Religious Education learning achievement in high school is still low because students are less enthusiastic, often postpone assignments, and teachers are less able to motivate students and prepare learning. Access to PAI material on the internet is still limited, and conventional learning methods make students passive, causing low learning outcomes. One solution to overcome this problem is to implement interactive e-modules based on live worksheets. This research aims to analyze planning, implementation, supporting factors,solutions, effectiveness of Implementing for the implementation of live worksheet-based interactive e-modules in Islamic religious education learning. This research uses an analytical narrative method with a qualitative approach. As for Data collection techniques are carried out through interviews, observation and documentation. The findings show that the implementation of Liveworksheet-Based Interactive E-Modules in Islamic Religious Education Learning at SMA Negeri 1 Cidahu requires steps including preparation, introducing the module to students, using the module in learning, evaluating student progress, and joint reflection for improvement. Different approaches are used to create an inclusive and effective learning environment. Full support from school leaders and teacher training supports implementation, while the obstacles are limited technological infrastructure and variations in teacher skills. To overcome these obstacles, support and collaboration between teachers is the key to overcoming these obstacles, and outreach to students is also part of the solution to increase their understanding.